The Identification and Analysis of Adverse Events in Elderly Female Breast Cancer Patients Using Anthracycline-Based Regimens at Dharmais Cancer Hospital - Ester Marsaulina Marsaulina; Retnosari Andrajati; Yuri Pertamasari; Alvinda Heriza Nasution (National Cancer Center - Dharmais Cancer Hospital, 2022)
Background: Anthracycline is the first-choice chemotherapy for the treatment of breast cancer, particularly in elderly patients. However, several studies reported adverse events in the treatment of using anthracyclines. This study aims to identify adverse events. It is also to find out more about how independent variables are related to adverse events. Method: An observational retrospective study of elderly patients (≥ 60 years old) was conducted in a tertiary cancer hospital in Jakarta. Data were collected from January 2018 to December 2020. We used an oncology-specific trigger tool to identify adverse events during anthracycline-based regimens. Independent variables were evaluated in univariate analysis: age, weight loss, marital status, total cumulative dose, polypharmacy, types of anthracyclines, and metastatic status. Bivariate and multivariate analyses were conducted to find out the relationship between the independent variables and adverse events.Results: In total, 107 subject records were collected and reviewed. Triggers were identified 122 times in 86 medical records. Blood transfusion, the most common trigger, was found in 35% of subjects. We found the number of triggers and adverse events more commonly identified in the first and second cycles of chemotherapy. The prevalence of adverse events is detected in 80% of subjects. Of these 86 subjects, 74% were detected in doxorubicin and 26% were detected in epirubicin. All the adverse events were categorized as The National Coordinating Council for Medication Error Reporting and Prevention (NCCMERP) harm category E.Conclusion: Trigger tools specific for cancer patients can be used to identify adverse events. Blood transfusion was the common trigger to detect adverse events in our study. Adverse events with category E were identified in all the subjects. Neutropenia and anemia were the most common adverse events in all cycles of chemotherapy. Weight loss was the independent variable related to adverse events in elderly breast cancer patients (p <0.003).